DESIGN OPTIMIZATION OF BILATERAL OPENING WITH INTERNAL BLINDS DEVICES TO INCREASE DAYLIGHT PERFORMANCE IN CLASSROOMS WITH TROPICAL CLIMATE USING RBFOPT ALGORITHM - Nur Hakim, Fahmi
In recent years, energy savings and environmental concerns have changed the perception on the use of electric lighting as the primary light source in buildings. Daylighting is now perceived to be a major factor in building design. School classrooms are examples where daylight is needed to ensure an effective teaching and learning process, especially for elementary school students who are more sensitive to light. In the tropical climate regions, daylight has a great potential to become the main light source in classrooms. This is because daylight in tropical climate regions is available throughout the year with relatively constant duration. However, if not controlled properly, daylight can cause visual discomfort, so that certain design strategies are required to control the amount of daylight in buildings. Several researchers have attempted to overcome the negative impact of daylighting. The use of complex shading devices such as internal blinds can significantly improve daylight quality and save energy in buildings. This is because the shading devices can prevent the entry of direct sunlight and can distribute daylight inside the room. Performance of the internal blinds is influenced by the design of the blades within the device. Earlier research on the internal blinds design in tropical buildings had been carried out, but the daylight simulation still implemented the 2PH Radiance matrix method. Meanwhile, internal blinds in buildings can be classified as a complex fenestration system, so that it is necessary to use the 3PH Radiance matrix method in simulating the daylight performance. However, the use of the 3PH Radiance matrix method for buildings with blinds is still limited in in non-tropical climate regions. Building design optimization method is required in order to achieve one with the best daylighting performance. Several optimization methods have been developed with different performances, where a performance comparison between other single-objective black-box optimization algorithms is carried out, where the Radial Basis Function Optimization (RBFOpt) algorithm has the best performance with a lower number of iterations and quite robust where these two things are quite important factors in the design of blinds that involve the phenomenon of a complex fenetration system. Therefore, it is necessary to optimize the design of bilateral openings with internal blinds, to improve daylight performance in a simulated tropical classroom using RBFOpt algorithm. In this study, the classroom buildings were modelled in two locations, namely Lhokseumawe and Bandung, at four building orientations, namely 0°, 45°, 90°, 135°, as well as with and without external shadings. Then, a sensitivity analysis was carried out to obtain the design parameters with the most influencing the design output. The design parameters consisted of the window to wall ratio (WWR), the ratio of the blind system area to the window area (BWR), the width of the blinds, the distance between the blinds, the of inclination angle of the blinds, depth and elevation of external shading. The daylighting performance are represented by metrics ASE1000,250, sDA300/50%, UDI100-3000lx, UDI250-750lx. Sensitivity analysis was conducted using standardized regression coefficients, followed with design optimization of bilateral openings with blinds in both classroom types using RBFOpt algorithm. In the initial condition where the openings are without blinds, the simulation results show that there is excessive direct sunlight in the classroom, especially in areas close to the opening as indicated by the ASE1000,250 . Results of the sensitivity analysis show that the parameters of WWR and BWR most influencing the daylight performance in classrooms without external shadings. In the classrooms with external shadings, WWR, BWR, and shading elevation become the most influential parameters. Then, based on the design optimization, the optimum WWR value is within the range of 15% - 25%, the optimum BWR value is within the range of 75% - 100%, and the values of WWR, BWR, and elevation of the shade are higher in conditions of relatively more sunlight. The optimum daylight performance metrics are ASE1000,250 within 0% - 3.6%, sDA300/50% of 100%, UDI100- 3000lx within 88.5% - 99.5%, and UDI250 -750lx within 70.4% - 91.7% in both building locations, four building orientations, and both classroom types.